2012
DOI: 10.1200/jco.2011.40.2792
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Children With Metastatic Medulloblastoma Treated With Carboplatin During Craniospinal Radiotherapy: A Children's Oncology Group Phase I/II Study

Abstract: A B S T R A C T PurposeWe evaluated the feasibility of administering carboplatin as a radiosensitizer during craniospinal radiation therapy (CSRT) to patients with high-risk medulloblastomas (MBs) and supratentorial primitive neuroectodermal tumors, and we report the outcome in the subset with metastatic (Mϩ) MB. Patients and MethodsAfter surgery, patients received 36 Gy CSRT with boosts to sites of disease. During radiation, patients received 15 to 30 doses of carboplatin (30-45 mg/m 2 /dose), along with vinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
148
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 18 publications
3
148
1
1
Order By: Relevance
“…For example, as chemosensitizers, temozolomide and bevacizumab have been used concurrently with radiation therapy in high-grade gliomas, and carboplatin has been studied as a radiation sensitizer with medulloblastomas and other CNS tumors. [19][20][21][22] In addition, chemotherapeutics such as anthracycline and doxorubicin are commonly avoided during radiation and can even remotely result in radiation recall with a later insult. 23 Finally, there are many chemotherapeutics that may have direct CNS toxicity such as methotrexate and ifosfamide, which could potentiate CNS radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as chemosensitizers, temozolomide and bevacizumab have been used concurrently with radiation therapy in high-grade gliomas, and carboplatin has been studied as a radiation sensitizer with medulloblastomas and other CNS tumors. [19][20][21][22] In addition, chemotherapeutics such as anthracycline and doxorubicin are commonly avoided during radiation and can even remotely result in radiation recall with a later insult. 23 Finally, there are many chemotherapeutics that may have direct CNS toxicity such as methotrexate and ifosfamide, which could potentiate CNS radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors shown to influence survival include histological subtype, age at diagnosis, and therapy utilized. The majority of publications on survival of medulloblastoma describe results of clinical trials, which have stringent eligibility criteria that necessarily influence the survival data [5][6][7][8][9]. As well, the majority of medulloblastoma studies are for specific age ranges, usually over age 3 or under age 3, and not for the whole population of affected children.…”
Section: Introductionmentioning
confidence: 99%
“…5,24 There is also evidence to suggest that standard or highdose chemo therapy can injure the normal brain, 9 and there appears to be a compounding effect when radiation therapy and che motherapy are used together. 3,14,15,17,20 In a Phase I/II study evaluating the use of carboplatin during radiation therapy in patients with medulloblastoma, the authors found 4 metastatic patients with early progression of leptome ningeal disease who were longterm survivors following palliative chemotherapy alone. The authors, in retrospect, stated that these patients were not believed to have true progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors, in retrospect, stated that these patients were not believed to have true progressive disease. 15 Additionally, there is increased evidence of clini cal and radiographic therapyrelated alterations as a re sult of the more frequent use of highdose chemotherapy combined with radiation therapy for pediatric brain tu mors. 16,25 Our patient was observed to have clinical symp toms and radiographic changes more than a year after therapy.…”
Section: Discussionmentioning
confidence: 99%